Practices of Financial and Management Accounting: Evidence fromSmall and Medium-Sized Enterprises of Nepal (Journal of Nepalese Business Studies, 2016)
76     One of the important factors which determine the performance of a business  organization is effective use of financial and management accounting system.  In Nepal, very few published evidence on the accounting practices among small and medium sized enterprises (SMEs) is found. In this regards, this study aims to examine the financial and management accounting practices among SMEs in Nepal and to investigate perceived usefulness of these reports for decision making process. A survey was carried out using the SMEs in the various nature of business listed by industrial statistics as sampling frame. The findings from  the study has provided relevant and useful insights about the current financial  and management accounting practices and the level of perceived usefulness of the accounting reports among SMEs. The result of the study indicates that a majority of the SMEs surveyed prepare their accounting reports at least one times in a year.  Man agement accounting reports were perceived to be more useful and decision making tool than financial accounting reports. Among the financial accounting reports, profit and loss statement was considered as most useful, followed by balance sheet and cash flow. It also found that there is no significance mean difference of practices of each accounting system across three types of SMEs.Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp. 77-86